2014
DOI: 10.2298/spat1432001s
|View full text |Cite
|
Sign up to set email alerts
|

Glulam beams reinforced with FRP strips and their application in architecture

Abstract: This paper emphasizes the advantage of using carbon polymers while producing and strengthening glulam beams. Due to advanced research carried out in this field, the first application of carbon polymers based products was implemented in Western countries. Structural elements containing carbon polymers, or being reinforced by them, show higher resistance and durability properties, as well as the ability to be produced in various shapes. These features can find best application in architecture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Additionally, other studies have reported results on the condition of FRP sheets placed in slits from the outside. [21][22][23][24][25] Nowak et al 23 conducted a study with CFRP sheets embedded in lateral slits in the tensile zone; three sheets were inserted on each side, and an approximately 21% increase of the flexural capacity was obtained, with a significant increase of the midpoint deflection and plastification area of the beam. Nowak et al 24 reported up to 19% improvements in flexural load capacity by expanding these results for the case of reinforcement vertically inserted in slits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other studies have reported results on the condition of FRP sheets placed in slits from the outside. [21][22][23][24][25] Nowak et al 23 conducted a study with CFRP sheets embedded in lateral slits in the tensile zone; three sheets were inserted on each side, and an approximately 21% increase of the flexural capacity was obtained, with a significant increase of the midpoint deflection and plastification area of the beam. Nowak et al 24 reported up to 19% improvements in flexural load capacity by expanding these results for the case of reinforcement vertically inserted in slits.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature is examined, many studies on wooden beams are formed as solid, 5,8,[13][14][15][16][17][18][20][21]24,[30][31][32] and there are many scientific studies in this area. When examined in Table 1, 4,13,19,22,25,29,34 glulam wood layers, which are more preferred in practice and less in academic studies, draw attention. Seven 27 and ten 33 glulam wood layers are less preferred, and as the number of layers increases, the weakness points at the interfaces increase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous works have demonstrated the importance of the quality of the wood used in laminated lumber under bending stresses [15]. The use of carbon and basalt fiber reinforced polymers (CFRP and BFRP, respectively) has been studied in sawn wood and technological products such as glulam and LVL elements, demonstrating the improvement of mechanical properties under different reinforcement configurations [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the existing wooden structures are made of pine, being the Pinus Sylvester widely used in many areas of the Iberian Peninsula. For several decades, many works have demonstrated the enormous advantages of FRP (fiber reinforced polymer) composite materials for retrofitting and repairing of structural elements (mainly beams) of concrete or timber, whether embedded in the structural element by means of artificially grooves (near-surface mounted technique), or externally applied (usually on the tension face but also on lateral sides of the element for shear reinforcement) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%